Video production handbook - Owens, Jim, 1957- (Focal Press, 2012)
Synopsis: Techniques matter! Great ideas don't automatically translate into great programs. It's not enough simply to show what is going on. The way you present your subject will influence how your audience responds. You need to choose your picture and sound carefully, to convey your ideas in an interesting, persuasive way. This book will show you how. Video Production Handbook shows the full production process, from inception of idea to final distribution. The book focuses especially on why each step occurs as it does and provides guidance in choosing the simplest methods of creating the shots you want in your video project. Concentrating on the techniques and concepts behind the latest equipment, this book demonstrates the fundamental principles needed to create good video content on any kind of budget. Suitable for students and beginning videographers, the new edition of this classic text retains its clarity and directness but has been completely revised and updated. This practical sourcebook has been specially prepared to give you an at-a-glance guide to quality video program-making on a modest budget. Emphasis throughout is on excellence with economy; whether you are working alone or with a small multi-camera group. The well-tried techniques detailed here will steer you through the hazards of production, helping you to avoid those frustrating, time-wasting problems, and to create an effective video program. Highly visual: more than 450 full color photos and illustrations demonstrate techniques; Modern: Revised by Jim Owens, who brings a wealth of hands-on experience to the text; up-to-date information on current equipment, techniques, and new distribution outlets such as the Web and mobile phones; A complete resource: Detailed teaching ancillaries are available for instructors, including instructor's manual, test bank, sample syllabi, image collection, video content, and more; Brand new coverage of contemporary distribution methods; Interviews featuring industry professionals provide students with inside knowledge of the industry; Sidebars featuring new coverage of topics such as shooting for 3D, shooting with HDSLRs for video, and much more!; Highly visual: hundreds of full-color illustrations demonstrate techniques; Modern: Up-to-date information on current equipment, techniques, and new distribution outlets such as the Web and mobile phones; Balanced: Production techniques are covered in detail, but ideas and creative problem solving are given equal weight; A complete resource: Detailed teaching ancillaries are available for instructors.